Manfaat Taman Suropati Kota Jakarta Pusat Berdasarkan Persepsi Masyarakat Sekitar - Arvi Nabiel Setyananda; Parfi Khadiyanto (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
In general in every big city has green open space that can be utilized as one of public space for society. Green open space is also an important thing in the formation of urban structures, especially in urban areas. This is because the RTH has an important role in an urban area that is there are benefits such as social, cultural, economic, aesthetic and support ecological activities. Taman Suropati Kota Jakarta has an area of 16,328 m². Visitors who come to the park pretty much especially at night. Visitors who visit Suropati Park still do not understand the benefits of the park. In this study aims to assess the benefits of Taman Suropati Kota Jakarta Central to the surrounding community is in accordance with its function or not by looking at PERMEN-PU no. 05 / PRT / M / 2008 on Guidelines for the Provision and Utilization of Green Open Space in Urban Areas based on visitor perceptions and research preferences. Taman Suropati still has ecological, social and cultural benefits which has 13 indicators in it. Taman Suropati Kota Jakarta in this case is good in ecological, social and cultural benefits, because only some of the indicators that have problems to be solved by Central Jakarta Municipality government.